Communication problems in creating awareness among the public in the justice process from a case study of the draft bill to repeal the Act on Offenses Relating to the Use of Checks B.E. 2534 - Arayasantiparb, Anthayakorn; Puengklom, Khanit; Purksametanan, Jitiya; Keawsomchat, Surisa; Class 19, Intermediate Justice Course (Journal of the Association of Researchers, 2024)
This research aims to study the communication of agencies in the justice process to the public of the draft bill on the repeal of the Act on Offenses Relating to Cheques B.E. 2534 and present innovative solutions to the problem. A qualitative study was conducted, which was a synthesis of documents and in-depth interviews with key informants, such as the general public, those who had been prosecuted in cheque cases, law enforcement officers, lawyers, the media, and a sample group of 101 people involved in the case. The analysis and presentation of the results were descriptive statistics. The results of the study found that more than half of the respondents did not know and did not know what stage the draft bill on the repeal of the Act on Offenses Relating to Cheques B.E. 2534 was in. The solution using “innovative solutions” should increase the missions of the department responsible for public relations and communication, which must have knowledge and skills in Digital Marketing to use in measuring results. The innovation consists of 1) process innovation, agencies responsible for public relations and communication, both before and after the law is enacted, in a format that recipients can understand through all channels, such as electronic media, social media. There must be the creation and promotion of government personnel responsible for communicating information to have good communication skills, such as knowledge of Digital Marketing. 2) technological innovation The Ministry of Justice's public relations should have channels for public relations and communication before and after legislation is enacted by creating an application for online legal Q&A to help the general public, such as AI, Chat GPT, and Machine Learning. We request cooperation from all mobile phone networks to provide notifications every time, which have a time frame and indicators.